(untitled) (International Journal of Engineering Materials and Manufacture, 2025)
Piezoelectric materials have the unique ability to convert mechanical energy into electrical energy and vice versa, allowing them to both generate electricity under stress and deform in response to electrical stimulation. This dual functionality makes them a highly promising candidate in biomedical engineering. Over the past few decades, researchers have explored their potential for applications such as tissue engineering, artificial muscles, biomedical implants, and bone tissue regeneration. The growing demand for self-powered and biocompatible devices has increased interest in these materials as they can operate without external power sources by harvesting energy from natural body functions. However, a major research gap remains in developing biodegradable and non-toxic piezoelectric materials that integrate safely into living tissues while maintaining sufficient mechanical strength and electrical responsiveness. Many studies have focused on electrical performance, with less emphasis on long-term biocompatibility and degradation in biological environments. This review analyses the properties and biomedical applications of piezoelectric materials, specifically their biocompatibility, biodegradability, and electromechanical characteristics in skin and neural regeneration, artificial muscles, pacemaker and cochlear implants, and bone tissue regeneration. Future research should prioritize non-cytotoxic, biodegradable composites that balance biocompatibility and performance. Advancements in this area could revolutionize biomedical devices by enabling self-powered, responsive healthcare solutions.